Framing the roles and responsibilities of excellent teachers: evidence from Malaysia - Tengku Ariffin, Tengku Faekah; Bush, Tony; Nordin, Hasniza (Elsevier, 2018)
This paper is based on a study of the role and responsibilities of excellent teachers, as described by the teachers themselves and their role sets (Merton 1957). The data collected via the semi-structured interviews with the teachers were triangulated with documents which show official expectations of excellent teachers. Data were also compared with interviews carried out with other teachers, school administrators and the inspectors, to provide a 360-degree view on the roles and responsibilities of excellent teachers. Five themes emerged from the data analysis, respectively focusing on their roles as teacher, context expert, facilitator, mentor, and innovator.